CNS tuberculoma mimicking brain metastasis - Gautam, Vinod Kumar Singh; Shrivastava, Ankur; Khare, Akriti; Singh, Ravinder (International Journal of Medicine, 2014)
A 32 year old male patient, a follow up case of carcinoma tongue post radiotherapy, presented with history of non-healing ulcer on lateral aspect of neck since 2 years and recurrent episodes of seizures for about 13 months duration. Neuroimaging was suggestive of metastasis in brain and patient was referred to us for biopsy of the lesion. Detailed clinical and radiological work up followed by neurosurgical intervention established the diagnosis of neurotuberculosis. In a patient with primary systemic malignanacy with suspected central nervous system metastasis, brain tuberculoma should always be kept as a differential diagnosis. Keywords: Brain Metastasis, Carcinoma Tongue, Tuberculoma.